Thromboxane Biosynthesis, Neutrophil and Coagulative Activation in Type IIa Hypercholesterolemia - Davì, Giovanni; Ganci, Antonina; Averna, Maurizio; Giammarresi, Carlo; Barbagallo, Carlo; Catalano, Isabella; Calà, Anna; Notarbartolo, Alberto (Thrombosis and Haemostasis, 1995)
Thromboxane (Tx) A2 biosynthesis is enhanced in the majority of patients with type IIa hypercholesterolemia. Because blood clotting activation is an important component of the inflammatory response, involved in the initiation and progression of atherosclerotic plaques, we have investigated TxA2 biosynthesis, neutrophil activation and thrombin generation in 24 patients with type IIa hypercholesterolemia.Urinary 11-dehydro-TxB2, was significantly higher (p =0.0001) in patients than in 24 sex- and age matched healthy subjects. Similarly, prothrombin fragment 1+2 (F1+2), thrombin-antithrombin III complexes and plasma elastase were significantly higher in patients than incontrols. Urinary 11-dehydro-TxB2 excretion was correlated with plasma elastase (r = 0.758; p =0.000I), and prothrombin fragment 1+2 (r = 0.804; p = 0.001). The enzyme 3-hydroxy-3-methylglutaryl coenzyme A reductase inhibitor simvastatin (20 mg/day for 2 months) significantly reduced cholesterol levels, urinary 11-dehydro-TxB2 excretion, plasma elastase and plasma Fl+2 in 8 patients.We conclude that type IIa hypercholesterolemia is associated with biochemical evidence of platelet, neutrophil and blood clotting activation. The relationship between these events remains to be investigated.